Pedometry applied to a comparative study using morphine and tramadol in bovine - Nogueira, Geison Morel; Perri, Sílvia Helena Venturoli [UNESP]; Santos, Paulo Sérgio Patto Dos [UNESP]; Rodrigues, Celso Antonio [UNESP] (FapUNIFESP (SciELO), 2019)
The use of opioids for analgesia is limited or undefined in ruminants. The aim of this study was to compare two analgesics opioids, morphine and tramadol, based on the clinical and pedometric evaluations of animals submitted to a temporary experimental arthritis and synovitis, developed at the distal interphalangeal joint after an intra-articular administration of amphotericin B. Six animals were used in two different treatments, using morphine, dose of 0,5 mg/kg, and twenty days later, tramadol, dose of 1,8 mg/kg, both intramuscularly. The animals were evaluated at 3-hour intervals for a total of 27 hours, observing the physiological parameters, ambulation and pedometer activity. Lameness and pedometer variations were observed in both treatments. Based on the variables of pedometric activity, a pattern of restlessness compatible with podal nociception was observed, and there was no interference of any of the drugs on lameness. It was concluded that morphine and tramadol, at the tested doses, were incapable of interfering in the lameness attenuation during the maximum painful stimulation moment in this experimental protocol of orthopedic pain.
Pedometria aplicada a estudo comparativo entre morfina e tramadol em bovinos
Keywords: Amphotericin B; Arthritis; Lameness; Pain; Synovitis